Strategy to Improve MSME Export Performance through Training and Capacity Building at the Kur Dodik Alfi Rope Bag Craft Center in Blitar Regency - Hery Suprayitno; Sudarmiatin; Heri Pratikto (Kirana Publisher (KNPub), 2026)
This study aims to analyze strategies for improving the export performance of Micro, Small, and Medium Enterprises (MSMEs) through training and capacity building at the Dodik Alfi macramé bag craft center in Blitar Regency, Indonesia. Using a qualitative case study approach, data were collected through in-depth interviews, observation, and documentation involving key informants, including business owners, training managers, and MSME actors. The findings reveal that MSMEs are still at an early stage of internationalization, with limited and irregular export activities. Although the products possess strong competitive advantages, such as unique designs, high aesthetic value, and handmade characteristics, export performance is constrained by limited internal capacity, including lack of export knowledge, absence of product standardization, and insufficient production capacity. Training programs have improved technical skills and product innovation; however, they have not significantly enhanced export performance due to the lack of integration with export-specific competencies, such as international marketing, logistics management, and regulatory compliance. The study proposes an integrative model in which training enhances internal capacity, which subsequently influences export strategy and performance. Export is identified as the most feasible initial strategy, with potential development toward licensing and franchising in the long term. The study highlights the importance of aligning training programs with export needs and strengthening institutional support to accelerate MSME internationalization